Logic vs Aesthetic: The Effect of Environmental Claim and Visual Design in Green Advertising - Hashella Kostan; Alice Salendu (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
The surge in demand for green products leads to rampant practice of â€œgreenwashingâ€, in which marketers deceitfully try to position their brand as more eco-friendly than it actually is. Past studies on green advertisements have indicated that visual cues in the advertisements can also play a part in affecting consumersâ€™ evaluation of the product and its eco-friendly feature. This study was conducted to examine the effect of two essential elements in a green advertisement, which are the overall visual aesthetic quality of the advertisement and verbal environmental claim. The study was conducted using an experimental vignette method. Two hundred seventy-six respondents participated in this study. Through MANOVA statistical analysis, it was found that both aesthetic quality and environmental claim type used significantly affect green brand associations, as well as the attitude respondents, have towards the brand. However, this significant effect of ads visual aesthetic quality can be concerning since it might hinder consumers to objectively evaluate the environmental claim of the product.